1997
DOI: 10.1038/bjc.1997.371
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral metastases of cutaneous melanoma

Abstract: Summary Cerebral metastases of cutaneous melanoma carry a very poor prognosis. We report our experience of 31 patients who presented with cerebral metastasis of cutaneous melanoma in a 5-year period between mid-1991 and mid-1996. Cerebral metastases were diagnosed on computerized tomography (CT) scan after patients became symptomatic. The overall median survival in our series was 4 months. Seventeen patients (55%) received treatment with radiotherapy and dexamethasone with resolution of their symptoms, althoug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
30
0
4

Year Published

1999
1999
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 19 publications
1
30
0
4
Order By: Relevance
“…The median overall survival of approximately 7 weeks is similar to that quoted by other authors who have reported median survivals of between 9 and 20 weeks (Madajewicz et al, 1984;Choi et al, 1985;Ziegler and Cooper, 1986;Barth et al, 1995;Gupta et al, 1997;Ellerhorst et al, 2001). Clearly, in a situation with such a poor prognosis, it is important to attempt to deliver treatment according to rational guidelines based on the likelihood of gaining a palliative benefit.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The median overall survival of approximately 7 weeks is similar to that quoted by other authors who have reported median survivals of between 9 and 20 weeks (Madajewicz et al, 1984;Choi et al, 1985;Ziegler and Cooper, 1986;Barth et al, 1995;Gupta et al, 1997;Ellerhorst et al, 2001). Clearly, in a situation with such a poor prognosis, it is important to attempt to deliver treatment according to rational guidelines based on the likelihood of gaining a palliative benefit.…”
Section: Discussionsupporting
confidence: 83%
“…The largest reported series of WBRT in MMM is by Sampson et al (1998) who treated 180 patients with a median survival of 120 days. Other smaller series report similar median survivals in the range of 9 -20 weeks (Madajewicz et al, 1984;Choi et al, 1985;Ziegler and Cooper, 1986;Barth et al, 1995;Gupta et al, 1997;Ellerhorst et al, 2001). Numerous studies of the effects of fraction size on palliation and survival have failed to demonstrate a survival advantage and many authors recommend a total dose of at least 30 Gy (Ellerhorst et al, 2001).…”
mentioning
confidence: 93%
“…These results are consistent with the data from the literature. The prognostic relevance of these three prognostic factors has been described before in patients with brain metastases from melanoma (2,3,6,8). In addition, KPS has been suggested as a relevant prognostic factor for OS (3).…”
Section: Discussionmentioning
confidence: 98%
“…Treatment approaches to metastatic malignant melanoma include systemic therapy (23,24) as well as local treatment such as stereotactic radiotherapy (25) and surgery (26,27) for patients with solitary brain metastasis and absent or stable extracranial disease (28). Patients with inoperable or multiple brain metastases may be candidates for WBRT (29) which is also part of the multimodal treatment concept of metastatic malignant melanoma (21,30,31) with an expected median survival of 2.5-4 months after hypofractionated radiotherapy (32) as opposed to steroid therapy alone (33,34). however, both the treatment sequence and the decision for a validated standard approach of combined therapy in metastasized melanoma can be challenging (35,36).…”
Section: Introductionmentioning
confidence: 99%